Gene editing and CRISPR-dependent homology-mediated end joining - Brian L. Ruis; Anja K. Bielinsky; Eric A. Hendrickson (Experimental and Molecular Medicine)
Abstract Gene editing is the intentional modification of a genetic locus in a living cell and is used for two general applications of great importance and wide interest. One is the inactivation of genes (‘knockouts’), a process utilized to delineate the loss-of-function phenotype(s) of a particular gene. The second application (‘knock-ins’) is essentially the process of gene therapy, which predominately involves correcting a pre-existing mutated allele(s) of a gene back to wild-type to ameliorate some pathological phenotype associated with the mutation. Importantly, although these applications are conceptually exact reciprocal opposites of one another, they are achieved via mechanistically different pathways. In the case of knockouts, breakage (usually in the form of double-stranded breaks) of the chromosomal DNA at the site of targeting is used to engage a repair process (nonhomologous end joining) that is error prone. The ensuing repair frequently results in insertions/deletions at the cleavage site, which, in turn, results in out-of-frame mutations and, hence, a knockout of the gene in question. In the case of knock-ins, breakage (again, usually in the form of double-stranded breaks) of the DNA is used to engage a repair process (homology-dependent repair/recombination) in which homologous sequences between an incoming donor DNA (containing new genetic information) and the chromosomal DNA are exchanged. Although homology-directed repair was known to predominate in bacteria and lower eukaryotes, the competing process of nonhomologous end joining predominates in higher eukaryotes and was presumed to prevent the use of knock-in gene editing in human somatic cells in culture. A series of molecular and technical advances disproved this notion but still resulted in a process that was cumbersome, labor intensive, highly inefficient and slow. In 2013, however, a new RNA-programmable nuclease, CRISPR–Cas9 was described that has revolutionized the field and made gene editing accessible to anyone with even a rudimentary knowledge of molecular biology. Thus, gene editing in a wide variety of model organisms, as well as human somatic cells in culture, has become not only extremely feasible but also extremely facile, and it harbingers a golden age for directed mutagenesis, directed evolution and improvements in gene therapy.